Letter (copy) : Help for the Workers of Spain Fund - Tewson, Vincent
028-0241-001 Our Ref: HVT/FC/805. 30th July, 1936. Mr. J. E. Gartside, J.P., Secretary, The Saddlesworth & Dist. Weavers' & Woollen Textile Workers' Association, Green Lane, Delph, Nr. Oldham. Dear Mr. Gartside, HELP FOR THE WORKERS OF SPAIN FUND. I have your letter of the 29th instant referring to the above matter enquiring as to whether a grant to the above Fund would be regarded as for political purposes. You will be quite safe in making a donation from your Industrial Fund as the money is to be used strictly for the relief of distress and consequently does not come under any items laid down in the 1913 Act for which only political funds can be used. Yours sincerely, for Joint Secretary. 292/946/28/241